MARKETING SRATEGY AT MANGO DAY BY USING SWOT ANALYSIS METHOD - Dila Sari Annisa; Irfan Ardiansah; Totok Pujianto (Jurnal Riset Bisnis dan Manajemen, 2021)
Mango Day is small medium industry that echoes a healthy lifestyle as one of their visions with fruit strip as their product made from dried mangoes. The purpose of this research is to get the best marketing strategy for the Mango Day business. This research is a qualitative research with data collection techniques for instance, interviews, observations, and documentation with analytic descriptive results. The SWOT analysis technique is used to process data to obtain alternative strategies. There are four alternative strategies that can be used by companies as the company’s latest marketing strategy. SO strategy: maintaining product quality and creating new product variants, ST strategy: intensifying marketing on social media and other E-commerce is inserted with knowledge of products to be affordable to all groups and to expand the spread of products offline. WO Strategy: improve the quality of packaging and WT strategy: improve production processes to industrial scale